The impact of performance measurement on purchasing group dynamics: The Canadian experience. Issue 1 (January 2017) - Nollet, Jean; Beaulieu, Martin; Fabbe-Costes, Nathalie
Abstract: Purchasing groups were first created in the healthcare sector, which has faced unprecedented challenges in terms of cost control for over two decades. Purchasing groups are indeed supposed to generate additional savings and more efficient purchasing processes. However, although various aspects of purchasing groups have been studied since the early 2000s, both their performance measurement and the influence that this measurement has on inter-organizational dynamics have been neglected. In purchasing groups, the dynamics between the group itself and its members often results in tensions between both parties. Performance measurement within purchasing groups could alleviate those tensions, since "objective" data could then be used to improve communication. Based on a case study, this research sheds light on performance measurement in a purchasing group, on the dynamics between the group and its members, and on the interaction between performance measurement and inter-organizational dynamics. Results indicate that measuring performance impacts the dynamics between both parties, but that the relationship is also the other way around, and that the inter-organizational dynamics is quite complex. In addition, this paper proposes a framework summarizing the research findings. Highlights: Developing purchasing group (PG) performance measures is complex. In a PG, inter-organizational dynamics should consider relationships among members. In Quebec healthcare, PG performance measurement systems appear to be rudimentary. Following savings more systematically might result in more satisfied PG members. Performance measurement and inter-organizational dynamics in PG are intertwined.